DIGITAL INNOVATIONS AND THEIR IMPACT ON BANKS’ COMPETITIVENESS - Vovchak, Olha; Gongalo, Natalia (Socio-economic relations in the digital society, 2020)
This article substantiates the need to use innovations in the banking sector of Ukraine. Their role in the period of formation of the fifth stage of informatization of society and creation of new technological functioning of both national and world economy is defined. Theoretical analysis of the definitions of «innovation» and «banking innovation», considered the content of banking innovations currently used by banking institutions in Ukraine, revealed the advantages and disadvantages of their use in banking. The influence of the innovation component on ensuring the competitive advantages of Ukrainian banks and the place and role in the activities of banks in general, increasing the level of trust in them, customer loyalty and increasing the level of efficiency of their operation are studied. A study of the use of various digital technologies by Ukrainian banks in their activities was conducted and their rating place was determined, according to the study. The main risks that arise when introducing various innovations in the banking business are also identified and the factors that can directly or indirectly hinder the development of innovations in the banking sector of Ukraine are considered. The use of the most acceptable ways of banks’ transition to the blockchain system and digital technology «BigData», which are now widely used by leading banking institutions in the world, is proposed. It is proved that the main trends that will exist in mobile banking in the near future will be: banking programs, digital banks, voice technologies, biometric security, smart bots, cardless transactions, open banking, cooperation with high-tech companies and design. It is substantiated that in the near future, technologically obsolete banks, which do not start actively using innovations in their activities, will begin to lose their customers, which may lead them not only to reduced profits but also to bankruptcy and closure of the banking institution.